A study of the enablers and challenges in the implementation of e-learning policies in technical education, vocational and entrepreneurship training colleges in Zambia - Konayuma, Gabriel Syantema (School of Education, 2016)
This study investigated the enablers and challenges in the implementation of e-Learning policies in public technical education, vocational and entrepreneurship training (TEVET) institutions under the Ministry responsible for Vocational Education and Training in Zambia. The aim of this study was to explore how implementation of e-Learning policies in a developing context could be enhanced so as to lead to improved access to TEVET. The study was guided by the following research questions: what knowledge do managers and lecturers have of e-Learning; what are the key enablers and challenges in implementing e-Learning policy; what criteria do individuals/institutions use to make the decision to adopt or reject e-Learning innovations and how are decisions made in the implementation of e-Learning in the TEVET sector. The study used the Diffusion of Innovation (DOI) theory to answer the main research question in the study. The theory was used to gain insights into TVET implementers and policy makers motivations and actions. The study was qualitative with seven (7) individuals interviewed. In the study, interviews of TEVET managers and lecturers were conducted to provide the data required to answer the research questions.